The Global Registry of Acute Coronary Events, 1999 to 2009–GRACE. Issue 14 (29th May 2010) - Fox, K A A; Eagle, K A; Gore, J M; Steg, Ph G; Anderson, F A; ,
Abstract : The aim of GRACE was to provide a large multinational registry of the full spectrum of patients with acute coronary syndromes (ACS) in order to define patient characteristics and outcomes and derive predictive risk scores. The study was designed and administered by an independent steering committee; data analyses were performed under the guidance of the steering committee at the Center for Outcomes Research of the University of Massachusetts. Regular feedback regarding local, regional and international guideline and performance measures was provided to individual hospitals and clusters of hospitals. Regional and international benchmark data were available to all sites. Main GRACE involved 123 hospitals in 14 countries in North and South America, Europe, Australia and New Zealand. GRACE2 (Expanded GRACE) comprised 154 hospitals in Europe, North and South America, Asia, Australasia and China. Continuous recruitment and follow-up took place between 1999 and 2009. The first 10 -20 patients per site (depending on hospital size) were enrolled each month, resulting in the recruitment of 102 341 patients, who were categorized as having ST-segment elevation myocardial infarction, non-ST-elevation myocardial infarction or unstable angina. Standardized case report forms (datafax or electronic) were completed by trained study coordinators, and included fields relating to demographic factors, comorbid conditions, treatments and in-hospital and post-discharge (6-month) events. Blood sampling, genetic analyses and longer-term follow-up were undertaken in GRACE substudies. Prospective individual patient follow-up was carried out. All sites were audited locally; 10% of individual patient records were audited in a 2-year cycle. Less than 1% of 20 key baseline fields, and less than 1% of discharge diagnosis and discharge status data, were missing. Six-month follow-up was 85% complete. Publications and risk scores are available at http://www.outcome.org/grace . Proposals for specific analyses were considered, in competition, by an independent publications committee.